Direct estimates of disability-adjusted life years lost due to stroke: a cross-sectional observational study in a demographic surveillance site in rural Gadchiroli, India - Sudharsanan, Nikkil; Deshmukh, Mahesh; Kalkonde, Yogeshwar (BMJ open, 2019)
Objective: To directly estimate disability-adjusted life years (DALYs) lost due to stroke in rural Gadchiroli, India and measure the contribution of mortality and disability to total DALYs lost. - Design: Cross-sectional descriptive study using population census, vital registration and stroke prevalence data. - Setting A demographic surveillance site of 86 villages in Gadchiroli, a rural district in Maharashtra, India. - Participants Population counts and mortality information were drawn from a census and vital registration system covering a population of approximately 94 154 individuals; stroke prevalence information was based on a door-to-door evaluation of all 45 053 individuals from 39 of the 86 villages in the surveillance site. - Primary outcome measures Years of life lost (YLL), years lived with disability (YLD) and DALYs lost due to stroke. - Results: There were 229 stroke deaths among the total population of 94 154 individuals and 175 stroke survivors among the subpopulation of 45 053 individuals. An estimated 2984 DALYs were lost due to stroke per 100 000 person-years with a higher burden among men compared with women (3142 vs 2821 DALYs). Over three-fourths (80%) of the total DALYs lost due to stroke were between ages 30 and 70 years. YLL accounted for 98.9% of total DALYs lost. - Conclusions: There was a high burden of stroke in rural Gadchiroli with a significant burden at premature ages. These results reveal a substantial need for surveillance and improved preventive and curative services for stroke in rural India.
Gesehen am 28.02.2020